Hemozoin: Bioinspired High‐Performance Energetic Materials Using Heme‐Containing Crystals (Small 29/2015). Issue 29 (3rd August 2015) - Slocik, Joseph M.; Drummy, Lawrence F.; Dickerson, Matthew B.; Crouse, Christopher A.; Spowart, Jonathan E.; Naik, Rajesh R.
<x xml:space="preserve">Abstract</x> R. R. Naik and co‐workers create highly energetic, bioinspired nanomaterial composites using synthetic hemozoin crystals. Hemozin forms naturally in vivo by the Plasmodium falciparum parasite, the causative agent of malaria. On page 3539, synthetic hemozoin is employed as an oxidizing material for aluminium nanoparticles (nAl). Hemozoin rapidly oxidizes peptide‐functionalized nAl fuel (spherical particles), releasing energy. These bioinspired composites rival conventional man‐made oxidizing materials by offering higher activity, lower cost, ease of handling, and increased stability.